Effects of gradual weight loss on strength levels and body composition in wrestlers athletes - Miranda, K. A.; Gheller, R. G.; Da Silva, I. M.; Picanço, L. A.; Libardoni Dos Santos, J. O. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Few investigations have evaluated isokinetic torque after a period of weight loss in wrestlers. Thus, the current study sought to investigate the effects of gradual weight loss in the precompetitive period on isokinetic peak torque in the upper and lower limbs and body composition in wrestling athletes. METHODS: Eight elite athletes participated in the study (mean age 20.8±3.1 years). The athletes visited the laboratory on 2 occasions: during the period of weight maintenance (baseline) and during weight loss, in the precompetitive period (post). The variables analyzed were body composition through air displacement plethysmography (BOD POD) and peak torque (PT) of knee flexion and extension movements, and internal and external shoulder rotation in concentric action, at speeds of 60°/s and 180°/s, determined using an isokinetic dynamometer (Biodex Medical Systems; Shirley, NY, USA). RESULTS: A significant decrease was observed in body composition values, except lean mass. No significant differences were observed in the PT of the movements analyzed: Shoulder internal rotation (60°/s P=0.825; 180°/s P=0.245) and external rotation (60°/s P=0.149; 180°/s P=0.163) and knee extension (60°/s P=0.086; 180°/s P=0.630) and flexion (60°/s P=0.310; 180°/s P=0.239). CONCLUSIONS: Gradual weight loss did not affect the production of torque in the wrestlers before a competition. In addition, gradual weight loss contributed to a reduction in body fat, associated with an increase in percentage lean body mass.